Reforma agrária e desenvolvimento local: o Assentamento Nova Santo Inácio e Ranchinho no município de Campo Florido (MG) - Nomura, Mirian (2001)
The agrarian issue is still a recurring theme in the Brazilian scenario, land ownership remains concentrated, and with it economic and political power are concentrated, thus creating a dynamic that prevents a large part of the rural population from better living conditions, work and democratic participation in political decisions. The rural development model, based on the technological modernization of large estates, has caused and has had negative consequences for the environment, for the process of land and income concentration. In the 1980s and 1990s, the social and economic problems of the rural population are aggravated due to the partial nature of the modernization process, and what is worse, most of those excluded by this process go to the cities, swelling the peripheries, because they no longer provide jobs for this surplus population. Thus, agrarian reform, nowadays, represents not only a way of giving dignified living conditions and citizenship to an important part of the rural population, but also means a strategy for a new development model, now based on the local, a model that integrate countryside and city, rural and urban. Through the study of the impacts of the Nova Santo Inácio and Ranchinho settlement in the municipality of Campo Florido, it was possible to verify the multiplier effects of agrarian reform, that is, through the establishment of a settlement, the dynamism of the municipality's economy can be observed, since, there is an increase in agricultural production, an increase in the commercialization of different products (food, clothing, furniture, household appliances, agricultural products, construction materials, etc.), and an increase in different services (banking, drilling of wells, transportation, offices, etc.) . The process of fighting for land also brings to the settler the possibility of better representing his interests before society, gaining space in political decisions.